Is there a rationale to record lymphatic invasion in node-positive colorectal cancer?. Issue 9 (8th May 2012) - Betge, Johannes; Schneider, Nora I; Pollheimer, Marion J; Lindtner, Richard A; Kornprat, Peter; Schlemmer, Andrea; Rehak, Peter; Langner, Cord
Abstract : This study aimed to evaluate the prognostic significance of lymphatic invasion in colorectal cancers that have already spread to regional lymph nodes. 168 patients with node-positive tumours (colon, n=98; rectum, n=70) were retrospectively evaluated. Lymphatic invasion was assessed on H&E stained slides and univariable and multivariable analyses were applied. Lymphatic invasion was detected in 95 (57%) cases and was significantly associated with tumour and node classification and tumour differentiation. Patients with tumours showing lymphatic invasion had decreased progression-free survival (p=0.025) and cancer-specific survival (p=0.082). Stratified by location, lymphatic invasion was significantly associated with decreased progression-free (p=0.010) and cancer-specific (p=0.023) survival in colon cancers, yet not in rectal cancers. Multivariable analysis proved T4 (HR 2.18, 95% CI 1.40 to 3.39; p<0.001) and N2 (HR 1.68, 95% CI 1.07 to 2.66; p=0.03) as independent predictors of progression-free survival and T4 (HR 1.90, 95% CI 1.17 to 3.07; p=0.009), N2 (HR 2.27, 95% CI 1.38 to 3.73; p=0.001) and poor tumour differentiation (HR 2.18, 95% CI 1.39 to 3.43; p<0.001) as independent predictors of cancer-specific survival, while for lymphatic invasion no influence on outcome was noted. In conclusion, only tumour and node classification, and tumour differentiation proved to be independent prognostic variables in node-positive colorectal cancer and merit special attention in clinical decision-making.